Naandamo: Indigenous Connections to Underwater Heritage, Settler Colonialism, and Underwater Archaeology in the North American Great Lakes - Ashley Lemke; Mark Freeland (Heritage)
The North American Great Lakes offer a dynamic case study of inundated cultural landscapes. These bodies of water and the life around them have never been static. While submerged lands offer avenues for archaeological research, it is essential to first understand that these cultural landscapes have also been flooded with invasive power dynamics through settler colonialism. For example, the land and water systems in Anishinaabe Akiing (the northern Great Lakes) have fundamentally shifted from flourishing life systems to poisoned areas and now struggle to deal with invasive species. When seeking to learn from or otherwise engage Indigenous knowledge, it is essential to work from a perspective that takes all these changes into consideration. There are Indigenous communities who are interested in these inundated landscapes, and in this research, but a pause, naandamo, is needed to ethically consider the ongoing process of settler colonialism and Indigenous perspectives. Here we address ethical considerations for researchers participating in, or interested in participating in, submerged site research. By incorporating settler colonialism as a methodology of understanding, we will provide an ethical starting place for working with Indigenous communities and inundated landscapes.